Peningkatan Hasil Belajar Menggunakan Model Problem Based Learning (PBL) pada Siswa Kelas 5 SD - Monika Setiyaningrum (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2018)
The research is motivated by the lack of maximum student learning outcomes at SDN Salatiga. There are 23 student from 32 student who score bellow KKM below 70 with an average score of 56,5. There were 23 students from 32 students who got grades below the KKM which were under 70 with an average score of 56.5. The existence of these problems, then held an effort to improve learning so that student learning outcomes can improve through classroom action research. The type of research that will be used is Classroom Action Research (CAR) which is carried out in two cycles. Technique of collecting data using observation and test result of learning Result of research have increased percentage of learning result and student learning activity reaching KKM at cycle I and II increase. Teachers should use Problem Based Learning (PBL) learning models to improve student learning outcomes. Improve student learning outcomes.